The vaccine candidate BLSOmp31 protects mice against Brucella canis infection - Clausse, María (2013)
Canine brucellosis represents a major reproductive problem worldwide and it is considered a zoonotic disease. New approaches are therefore urgently needed to develop an effective and safe immunization strategy against Brucella canis. In the present study, BALB/c mice were subcutaneously immunized with the recombinant chimera rBLSOmp31 formulated in different adjuvants. The different strategies induced a vigorous immunoglobulin G (IgG) response, with high titers of IgG1 as well as IgG2. Besides, spleen cells from rBLSOmp31-immunized mice produced gamma interferon and IL-4, suggesting the induction of a mixed Th1-Th2. Vaccination with rBLSOmp31-IFA formulation provided the best protection levels comparable with that given by control vaccines. None of the immunization strategies induced serological interference in diagnosis. Hitherto, this is the first report that a recombinant vaccine confers protection against B. canis in mice.